Atención temprana a las necesidades del niño - Sirna Argumedo, Paola (2016)
It is necessary to observe the children from very young, and to provide them a timely care to the difficulties that it is presenting, either in the areas: emotional, giving them love and security; motorboat; language or sensory. Such earlyattentions can help the child to overcome his time lag and not to trigger other difficulties that do not help them develop and/or develop favorably in school.